PENGARUH BERBAGAI JENIS MULSA TERHADAP KEPADATAN HAMA LALAT BUAH (Bactrocera sp.) PADA TANAMAN CABAI (Capsicum annuum L.) - Alisa, Nur; Nasir, Burhanuddin; Toana, Moh. Hibban (AGROTEKBIS, 2019)
One of the pests that attack the pepper plants (Capsicum annum L.) is the fruit fly (Bactrocera sp.). The way of controlling fruit fly (Bactrocera sp.) that Is using various types of mulch.  The purpose of this research is to know the influence of mulch type to fruit fly density (Bactrocera sp.) on pepper plant (Capsicum annum L.).  This research was conducted in Sidera Village, Sigi Biromaru Subdistrict, Sigi District, Central Sulawesi Province. This research activity took place from May to September 2016. This research used a Randomized Block Design (RBD) consisting of four treatments repeated four times to obtain 16 units of observation. The results showed that black silver plastic mulch obtained a large population of fruit flies with an average of 13, 22, 31, 28, 24, 27, 34 and 39 and the intensity of fruit fly attack with an average of 1,04%, 1,04, 2,09%, 6,25%, 7,29%, 9,37%, 9,37%, 10,42% and 15 , 63% while the production of pepper plant obtained on the silver black silver treatment that is with an average of 75,00 ton/ha, 18,17 ton/ha, 98,33 ton/ha, 107,92 ton/ha.